2011
DOI: 10.1186/1743-422x-8-233
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of rotavirus infection in children with gastroenteritis attending Jos university teaching hospital, Nigeria

Abstract: This study was conducted to determine the incidence of rotavirus infection in children with gastroenteritis attending Jos university teaching hospital, Plateau State. A total of 160 children with acute diarrhea were selected by random sampling. Stool samples were obtained and assayed for rotavirus antigens by enzyme linked immunosorbent assay technique using standard diagnostic BIOLINE Rotavirus kit. Demographic data of parents were also recorded. Rotavirus were detected in faeces of 22(13.8%) children with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
65
10
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 10 publications
49
65
10
4
Order By: Relevance
“…This is similar to other studies in Nigeria where rotavirus was detected in slightly higher rates in male than in females (Aminu et al, 2008, Pennap andUmoh 2010;Junaid et al, 2011). Similar studies in other countries such as in South Western Iran (Kajbaf et al, 2013), and in Sudan (Magzoub et al, 2013) have reported higher detection rates of rotavirus infection in males than in females.…”
Section: Rotavirus Adenovirussupporting
confidence: 79%
See 1 more Smart Citation
“…This is similar to other studies in Nigeria where rotavirus was detected in slightly higher rates in male than in females (Aminu et al, 2008, Pennap andUmoh 2010;Junaid et al, 2011). Similar studies in other countries such as in South Western Iran (Kajbaf et al, 2013), and in Sudan (Magzoub et al, 2013) have reported higher detection rates of rotavirus infection in males than in females.…”
Section: Rotavirus Adenovirussupporting
confidence: 79%
“…This is in consistent with a number of similar studies in Nigeria ( The highest prevalence of rotavirus infection occurred in the age-group 7-12 months (7.7%). This age-group distribution is comparable to previous reports by Junaid et al, (2011) and Kajbaf et al, (2013) where they reported higher prevalence in children 7-12 months old. The least prevalence of rotavirus infection was observed in the agegroup 0-6 months.…”
supporting
confidence: 79%
“…The possible reason for this might be that more number of samples are collected from male children, but some researchers also support our study (Saravanan et al, 2004;Banerjee et al, 2006;Junaid et al, 2011).…”
Section: Season Age and Gender-wise Prevalence In Childrensupporting
confidence: 66%
“…Signs of dehydration include thirst, irritability, restlessness, lethargy, sunken eye, dry mouth and tongue, dry skins and fewer trips to the bathroom to urinate. Others include lack of interest in playing and extreme sleepiness, fast breathing and rapid heartbeat 12 . Diarrhea incidence remains a tremendous burden on children in low-and middle-income countries due to multiple determinants such as; child malnutrition, low socioeconomic status, maternal education, lack of safe drinking-water, inadequate sanitation and poor hygiene 11 .…”
Section: African Journal Of Reproductive Health September 2017; 21 (3mentioning
confidence: 99%
“…Diarrheal incidence has been found to be highest in the first two years of life and declines as a child grows older 11 . The occurrence of diarrhea comes with symptoms like vomiting, stooling and can quickly lead to dehydration in young children 1,12 . Signs of dehydration include thirst, irritability, restlessness, lethargy, sunken eye, dry mouth and tongue, dry skins and fewer trips to the bathroom to urinate.…”
Section: African Journal Of Reproductive Health September 2017; 21 (3mentioning
confidence: 99%